Valutazione farmacoeconomica dell’uso di tramadolo vs ketorolac nella gestione del dolore postoperatorio - Mantovani, Lorenzo G. (Farmeconomia. Health economics and therapeutic pathways, 2003)
This article represents the first evaluation that compares the economic consequences of managing postsurgical pain with tramadol or ketorolac in the Italian setting. The economic evaluation was based on 5 clinical trials that directly compared the efficacy and tolerability of tramadol and ketorolac treatments in different settings and that contained drug consumption data. Since the review of these data confirmed that their efficacy is comparable (tramadol showed a quicker onset of the analgesic action, which was not considered for the purposes of the economic evaluation), it was chosen to conduct a cost minimization analysis. The calculations were made considering two different drug acquisition costs: the hypothetical price for the hospital, computed by discounting 50% off the retail price, and the mean price really paid by hospitals according to the IHS. The analyses showed that, when the discounted price is applied, tramadol induces costs that are similar to those induced by ketorolac in 2/3 of the cases and lower in the remaining 1/3. Considering the mean price paid by hospitals, tramadol results economically more advantageous than ketorolac in all considered settings. In conclusion, ketorolac and tramadol are two effective and tolerable drugs in the management of post-surgical pain, although they differ in the adverse event pattern and in the rapidity of their action. In the Italian setting, tramadol appears to be economically more efficient, due to lesser consumption and lower drug acquisition costs.